Gaseous environment in LLAGN: modes of interaction with compact star nuclear population. Issue Volume 10:Issue S309(2014) (9th February 2015) - Zajaček, M.; Karas, V.; Šubr, L.; Kunneriath, D.; Eckart, A.
Abstract: The Galactic center, which serves as a paradigm of low-luminosity active galactic nuclei (LLAGN), hosts the Nuclear star cluster (NSC) that contains both young and more evolved stars. So far the population of the end-products of stellar evolution has not been observationally confirmed and studied, although there are hints of its presence. We study the distribution of interaction modes of a hypothetical population of neutron stars within the sphere of influence of the Sgr A* supermassive black hole (SMBH). The comparison of our models with future observations could be used to constrain the 3D structure of the Galactic center.